A novel method for high temperature measurements using fiber Bragg grating sensor - Reddy, Parne Saidi; Prasad, Ravinuthala L.N. Sai; Srimannarayana, Kamineni; Shankar, Madhuvarasu Sai; Gupta, Dipankar Sen (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
This paper reports the simulation, design and experimental analysis of a fiber Bragg grating (FBG) temperature sensor, making use of chemical composition grating (CCG), which ranges from room temperature to over 900 °C. The interrogation system of the sensor proposed is simple, effective and of low cost. The sensor head comprises FBG attached to a metal plate that will be strained due to change in the length of the plate with increase in temperature. The temperature is measured on the basis of the reflected Bragg wavelength shifts from the FBG. The dynamic range of the sensor is about 30 °C to 900 °C. The proposed sensor can be employed for monitoring the health of structural members at elevated temperatures. The dynamic range of the sensor can be increased to beyond 1500 °C by making use of FBG made up of sapphire instead of silicon fiber.
Optica Applicata, Vol. 40, 2010, nr 3, s. 685-692
Keywords: optyka; fiber Bragg grating; chemical composition grating; long period grating; broadband source; 3 dB coupler; optical spectrum analyzer